137k views
2 votes
X = 2y - 3 & 3x - 7y = -14

2 Answers

4 votes

Answer:

(7, 5).

Explanation:

x = 2y - 3

2y = x + 3

y = x/2 + 3/2

3x - 7y = -14

-7y = -3x - 14

y = 3/7x + 2

3/7x + 2 = 1/2x + 3/2

6/14x - 7/14x = 1.5 - 2

-1/14x = -1/2

1/14x = 1/2

x = 7

7 = 2y - 3

2y = 10

y = 5

3 * 7 - 7 * 5 = 21 - 35 = -14

Since this works, your answer will be (7, 5).

Hope this helps!

User Fireburn
by
4.9k points
4 votes

Answer:

(7, 5)

Explanation:

You can solve by substitution

3(2y - 3) - 7y = -14

6y - 9 - 7y = -14

-y - 9 = -14

-y = -5

y = 5

x = 2(5) - 3

x = 7

User Blech
by
5.8k points